Toward a New Future for Essential Oils - Napoli, Edoardo; Di Vito, Maura (Antibiotics (Basel), 2021)
[...]their use is avoided according to the prudence principle. Both A. rosaeodora EO and linalool did not exhibit a cytotoxic effect in BALB/c peritoneal macrophages, and both reduced nitrite levels in unstimulated cells, revealing a potential effect on nitric oxide production. The planktonic growth of E. coli was inhibited by EO, citral, and geraniol as per as the bacterial adhesion on stainless steel. [...]the antimicrobial activity of some hydrolates was evaluated in comparison with the corresponding EOs by Di Vito et al.